Building Third Generation Land Tools:Its4land, Smart Sketchmaps, UAVs, Automatic Feature Extraction, and the GeoCloud - Bennett, R.M. (2020)
A third generation of land tools is emerging: ‘its4land’ is part of the movement. The initiative aims to create seven new tools that further support faster, cheaper, easier, and more responsible land rights mapping. The tools are inspired by the continuum of land rights, fit-for-purpose land administration, and cadastral intelligence. The project is built around an ICT innovation process that incorporates a broad range of stakeholder groups with emergent geospatial technologies, including smart sketchmaps, UAVs, automated feature extraction, and geocloud services. By coupling the technologies, end-user needs and market forces, are better responded to. Backed by the European Commission, the work consists of a 4 year work plan, €3.9M in funding, and 8 consortium partners. The project is working with stakeholders from six case study locations in Ethiopia, Kenya, and Rwanda: tool development, prototyping, and demonstration is intended for local, national, regional, and international interest groups. The case locations include a mix of livelihoods and landscapes: urban, peri-urban, rural smallholder, and (former) pastoralist contexts are all included. This paper reports holistically on the first year of its4land activities: lessons from major achievements and barriers are outlined. Risks and future opportunities are also explored.